Global human trafficking : critical issues and contexts - Dragiewicz, Molly (Libros electrónicos en Ebscohost, 2015)
Human trafficking has moved from relative obscurity to a major area of research, policy and teaching over the past ten years. Research has sprung from criminology, public policy, women's and gender studies, sociology, anthropology, and law, but has been somewhat hindered by the failure of scholars to engage beyond their own disciplines and favoured methodologies.